Interactions Between Maternal, Paternal, Developmental, and Immediate Environmental Effects on Anti-predator Behavior of the Snail Physa acuta - Tariel, Juliette; Luquet, Émilien; Plénet, Sandrine (Frontiers in Ecology and Evolution, 2020)
Transgenerational plasticity, which occurs when the environment experienced by parents changes the phenotype of offspring, is widespread in animal and plant species. Both maternal and paternal environments can underlie transgenerational plasticity, but experimental studies unraveling how their effects interact together and with the personal (both developmental and immediate) environments are still rare. Yet unraveling these interactions is fundamental to understanding how offspring integrate past and present environmental cues to produce adaptive phenotype. Using the hermaphroditic and freshwater snail Physa acuta, we tested how predator cues experienced by offspring, mothers and fathers interact to shape offspring anti-predator behavior. We raised a first generation of snails in the laboratory with or without chemical predator cues and realized full-factorial crosses to disentangle maternal and paternal cues. We then raised the second generation of snails with or without predator cues and assessed, when adults, their escape behavior in two immediate environments (with or without predator cues) and activity in the immediate environment without predator cues. We found that personal, maternal, and paternal predator cues interacted to shape offspring escape behavior and activity. Firstly, for escape behavior, snails integrated the cues from developmental and parental environments only when exposed to predator cues in their immediate environment, suggesting that personal immediate experience must corroborate the risky parental environment to reveal transgenerational plasticity. For activity, this same hypothesis helps explain why no clear pattern of transgenerational plasticity was revealed, as activity was only measured without predator cues in the immediate environment. Secondly, a single maternal exposure to predator cues decreased offspring escape behavior while a single paternal exposure had no effect, surprisingly demonstrating sex-specific transgenerational plasticity for a simultaneous hermaphroditic species. Thirdly, when both mother and father were exposed, paternal cues were integrated by offspring according to their own developmental environment. The paternal exposure then mitigated the reduction in escape behavior due to the maternal exposure only when offspring developed in control condition. Overall, our study highlighted complex patterns of sex-specific transgenerational plasticity resulting from nonadditive interactions between parental, developmental and immediate experiences.